Negación, nominalizaciones y estados - Laura Ros García (Revista Española de Lingüística)
The main goal pursued in this article consists in analysing the interaction of the negative particle no with those Spanish nouns that denote a state. Firstly, those nominals which possess a nominalizer are addressed. We show that they accept being preceded by no and we describe the interpretation that arises with them in this case. Then, whether negation modifies the aspectual properties of this class of nominals is studied. Next, we provide an explanation for the behaviour of these nominalizations which is based on the interaction of negation with their structural configuration. Secondly, those nouns that lack a nominalizer are scrutinised. It is concluded that they reject co-occurring with no, and that, depending on their syntactic structure, this incompatibility can arise from the interruption of the constituent by negation or from their non-possession of verbal nodes.